Décentralisation De La Dialyse Au Sénégal : Expérience D’1 An Du Centre De Tambacounda A l’Est Du Pays - Yaya, Kane; Mokhtar Mbacké, Leye Mamadou; Moussa Tondi, Zeinabou Maiga; Tall, Lemrabott Ahmed; Maria, Faye; Moustapha, Cisse Mouhamadou; Fary, Ka El Hadj; Boucar, Diouf (European Scientific Journal, ESJ, 2016)
Hemodialysis has made numerous and significant progress in recent decades resulting in life expectancy increase (thirty or forty years). The aim of our study was to assess the treatment of acute and chronic hemodialysis in the reference center of Tambacounda. Patients and methods: This was a prospective study over a one-year period (April 2013 to March 2014) in the hemodialysis center of the regional hospital of Tambacounda, 450km away from Dakar. The study focused on epidemiological, clinical, paraclinical and scalable data. Results: Fifty-nine patients were involved in the study. The sex ratio was 0.85 (32F/ 27M). The mean age was 41.3 years [12-72 years old]. Nineteen patients were on dialysis treatment for acute renal failure (ARF) (32.2%) and 40 were chronic hemodialysis patients (67.79%). Fifty patients were under emergency dialysis (84.7%) including 17 in intensive care (28.8%). Most chronic hemodialysis patients had 3 sessions per week (98.3%). Only 9 patients were monitored in nephrology prior to dialysis (22%). Thirty-two patients had a femoral double-lumen catheter (54.23%), 6 patients used ordinary double- lumen jugular catheters (10.17%) and 3 received tunneled jugular catheters (5.09%). Eighteen patients had functional arteriovenous (AV) fistula (18.51%). The mean hemoglobin was 7 g/dl. Only 11 patients had erythropoietin-based therapy. In acute renal impairment there were 8 deaths (42.10%), whereas in chronic renal failure the fatality rate was 18.8% (n = 9). Conclusion: Our study has demonstrated the benefits of decentralizing dialysis treatment in the provinces. However there is a need to implement the accompanying measures, such as the availability of some essential medicines for all hemodialysis patients, and equipment of intensive care units.